2009
DOI: 10.1074/jbc.m805607200
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A Promotes Peptide Hormone Sorting to Mobile Granules in Constitutively and Regulated Secreting Cells

Abstract: Chromogranin A (CgA) has been proposed to play a major role in the formation of dense-core secretory granules (DCGs) in neuroendocrine cells. Here, we took advantage of unique features of the frog CgA (fCgA) to assess the role of this granin and its potential functional determinants in hormone sorting during DCG biogenesis. Expression of fCgA in the constitutively secreting COS-7 cells induced the formation of mobile vesicular structures, which contained cotransfected peptide hormones. The fCgA and the hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 45 publications
7
46
0
Order By: Relevance
“…Cell Culture-Pheochromocytoma PC12 cells, the variant sympathoadrenal cell line A35C (27), and the African green monkey kidney fibroblast-derived COS-7 cells (ATCC, CRL 1651) were routinely grown as described previously (10,20). Most experiments were performed on cells plated onto either poly-L-lysine (Sigma) plus collagen (Upstate)-coated 15-mm round glass coverslips (Fischer No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell Culture-Pheochromocytoma PC12 cells, the variant sympathoadrenal cell line A35C (27), and the African green monkey kidney fibroblast-derived COS-7 cells (ATCC, CRL 1651) were routinely grown as described previously (10,20). Most experiments were performed on cells plated onto either poly-L-lysine (Sigma) plus collagen (Upstate)-coated 15-mm round glass coverslips (Fischer No.…”
Section: Methodsmentioning
confidence: 99%
“…The following excitation and emission wavelengths were used for imaging: GFP and fluorescein-conjugated antibodies (green), ex 490 Ϯ 10/ em 528 Ϯ 38 nm; RFP, MitoTracker, and Alexa Fluor 594 antibodies (red), ex 555 nm/ em 580 nm; CFP (blue), ex 436 Ϯ 10/ em 465 Ϯ 30 nm; Hoechst 33342 (nuclear DNA stain, blue), ex 350/ em 461 nm. COS-7 cells were observed on a Leica SP2 upright confocal laser scanning microscope (DMRAX-UV) equipped with the Acousto-Optical Beam Splitter system and with 25, 40, and 63ϫ oil immersion objectives (Leica, Microsystems, Reuil-Malmaison, France) as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this water-soluble glycoprotein that co-secretes with catecholamines from adrenomedullary cells also provided the first direct evidence of exocytosis on the basis that these proteins could not be released in any other way (Banks and Helle 1965). This family has since grown to also include chromogranin B (CgB or SgI), secretogranin II (SgII or CgC), SgIII (or 1B1075), , SgV (or 7B2), SgVI (or NESP55), SgVII (or VGF), and pro-SAAS, which are also found in many other tissues such as the pituitary gland and islets of Langerhans, as well as in brain neurons (Taupenot et al 2003;Helle 2010;Zhao et al 2009;Montero-Hadjadje et al 2009). …”
mentioning
confidence: 99%
“…More studies performed in non-endocrine cells as well as in PC12 cells devoid of regulated secretory pathway (A35C cells) revealed that CgA expression induced the biogenesis of dense-core granular structures, distinct from lysosomes, containing CgA and co-expressed hormones, and able to release their content upon Ca 2? influx (Huh et al 2003;Beuret et al 2004;Courel et al 2006;Montero-Hadjadje et al 2009;Stettler et al 2009). In contrast, other studies reported that expression of CgA in non-endocrine cells induced its targeting to the constitutive secretory pathway (Malosio et al 2004).…”
Section: Chromogranin a And The Biogenesis Of Secretory Granulesmentioning
confidence: 99%